Animal feed solar cooker: Design and economics - Poonia, Surendra; Jat, N K; Ola, C M (Indian Farming, 2023)
The farming systems in arid western Rajasthan are largely livestock based. The feed concentrates are essential to maintain health and milk production of the mulching animals in particular. For boiling of animal feed, huge amounts of firewood, animal dung cake and other organic wastes are burnt which make it costly, time consuming and unhealthy practice of livestock rearing. In this regard, the abundantly available solar radiation in the region can be utilized for boiling animal feed. Therefore, a low-cost high capacity solar cooker was designed for boiling animal feed using solar energy. The solar cooker was found suitable for boiling 10 kg animal feed per day, which is sufficient for 5 cattle and its efficiency was observed to be 26.4%. This solar cooker was found to save around 91 man-days/year of farm women and 1059 kg of fuel wood/year which is equivalent to 3611 MJ of energy besides saving firewood and animal dung cake for alternative usages. Hence, the animal feed preparation through solar cooker not only reduces greenhouse gas emissions but also helps in fuel conservation and drudgery reduction. Moreover, the use of the solar cooker for animal feed would result in the reduction of the release of 1442.64 kg of CO2 savings/year.